PELAYANAN PROGRAM PENDIDIKAN SEKOLAH KEJAR PAKET C DI KABUPATEN PURWOREJO (Studi Kasus Kualitas Pelayanan di Pusat Kegiatan Belajar Masyarakat (PKBM) Dian Putri Waringin Jaya Kecamatan Bayan Kabupaten Purworejo) - Prio Dwi Wibowo; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Community Learning Activity Center (PKBM) Dian Putri Waringin Jaya is an educational unit that is assigned by the Department of Education, Youth and Sports Purworejo to provide universal school education programs Packet C in Purworejo. This study aims to find out about the quality of service in the PKBM Dian Putri Waringin Jaya Bayan district of Purworejo. This study uses descriptive qualitative research. The author is using five quality dimension to measure the services quality at society learning centre Dian Putri Waringin Jaya there are tangible, realibility, responsiveness, assurance, dan empathy. The services quality influenced by two factors, that are human resources factor and communication factor. The result of this research shows that services quality of package C school education at Society Learning Centre Dian Putri Waringin hasn’t done well completely as the five dimension that used by the author. It known by tangible, assurance, and emphaty dimension. The obstacles inside are the limit of human resources and Communication between employees who are less well established. Based on the result, the author recommend to PKBM Dian Putri Waringain Jaya Bayan district of Purworejo to fix some of the dimensions and factors assessed is still not optimal.